Duplex regnum Christi: Christ's twofold kingdom in reformed theology - Beeke, Jonathon D. (Studies in reformed theology, 2020)
"In this historical study, Jonathon D. Beeke considers the various sixteenth- and seventeenth-century Reformed expressions regarding the duplex regnum Christi (the twofold kingdom of Christ), or, as especially denominated in the Lutheran context, the "doctrine of the two kingdoms." While a sampling of patristic and medieval sources is considered, the focus is on select magisterial Reformers of the sixteenth century and representative intellectual centers of the seventeenth century (Leiden, Geneva, and Edinburgh). A primary concern is to examine the development of these formulations over the two centuries in question, and relate its maturation to the theological and political context of the early modern period. Various conclusions are offered that address the contemporary "two-kingdoms" debate within the Reformed tradition"--